Ectoparasitic fungi of Myrmica ants alter the success of parasitic butterflies - Tartally, András; Szabó, Norbert; Somogyi, Anna Ágnes; Báthori, Ferenc; Haelewaters, Danny; Mucsi, András; Fürjes-Mikó, Ágnes; Nash, David R (Scientific reports, 2021)
Exploitation of organisms by multiple parasite species is common in nature, but interactions among parasites have rarely been studied. Myrmica ants are rich in parasites. Among others, the ectoparasitic Rickia wasmannii fungus and the parasitic caterpillars of myrmecophilous Phengaris butterflies often infect the same Myrmica colonies. In this study, we examined the effects of R. wasmannii on the adoption, long-term development, and survival of P. alcon. In laboratory conditions, caterpillars introduced into nests of Myrmica scabrinodis uninfected with R. wasmannii survived significantly longer compared to caterpillars introduced into infected nests. In the field, joint infection was less common than expected if both parasites exploited M. scabrinodis colonies independently. Pre-pupal caterpillars of P. alcon were somewhat larger in nests infected with R. wasmannii than those found in uninfected nests. Based on these results it seems that R. wasmannii infection of M. scabrinodis affects the survival and development of P. alcon caterpillars, suggesting competition between these two ant parasites.
Keywords: životní prostředí; Environment; houby; Host-Parasite Interactions; Host Microbial Interactions; Animals; motýli; interakce mikroorganismu a hostitele; Butterflies; interakce hostitele a parazita; Fungi; zvířata; Ants; Formicidae